Stomach Cancer in a Patient with Chronic Lymphocytic Leukaemia - R. A. Maier; B. A. Bakirov; M. V. Timerbulatov (Креативная хирургия и онкология, 2019)
Introduction. Chronic lymphocytic leukaemia (CLL) is a malignant clonal lymphoproliferative disorder characterised by the accumulation of atypical mature CD5/CD19/CD23-positive B lymphocytes, predominantly in blood, bone marrow, lymph glands, liver and spleen. Chemotherapy protocols with the inclusion of nucleotide analogues, alkylating drugs and monoclonal antibodies are currently the standard of treatment. FCR (fludarabine, cyclophosphamide, rituximab) is one of the most effective protocols. CLL may lead to various immunologic disorders resulting in an increased risk of a malignant neoplasm. This paper aims to present a demonstration of a case of the combination of chronic lymphocytic leukaemia and stomach cancer, and an attempt to establish — based on literature data — a link between the diagnosed stomach adenocarcinoma and the main disease.Materials and methods. Authors have analysed the case history, laboratory and instrumental data and the treatment of a patient with chronic lymphocytic leukaemia and stomach adenocarcinoma.Results and discussion. The patient E., 63 yo, was diagnosed with chronic lymphocytic leukaemia in 2016. The patient was started on FCR chemotherapy protocol (Fludarabine, 70 mg days 2-4 of CT, Endoxan 500 mg days 2-4 of the cycle, Rituximab 700 mg day 1 od CT) in June 2018. When the patient came to the BSMU hospital for a chemotherapy cycle in August 2018, gastric endoscopy was performed; tissue pathology examination resulted in the diagnosis of stomach adenocarcinoma. A concilium of surgeons, oncologists and haematologists made a decision to perform a gastrectomy with the oesophageal resection and Roux anastomosis.Conclusion. Having used a clinical case as an example and reviewed available literature, the authors have demonstrated that either CLL or the immunosuppressed status served as the causal factors for the development of the adenocarcinoma. The development of stomach adenocarcinoma in patients with chronic lymphocytic leukaemia makes the course and outcome of the main disease much more severe. A decision regarding the management strategy for such patients has to make individually every time, taking into account the severity of the oncological disease; this impacts on the choice of the treatment protocol. All the cases of spontaneous remissions in patients with lymphocytic leukaemia must be screened extensively in order to facilitate early diagnosis of malignant neoplasms.